Bacterial Antimicrobial Resistance and Residues in Tilapia Farms from One Health Perspective - Hossain, Sabrina; Delamare-Deboutteville, Jerome; Rheman, Shafiq; Khor, Laura; Chadag, Vishnumurthy Mohan (WorldFish, 2024)
The objective of the present study was to isolate One Health significant bacteria from tilapia-dominant polyculture food production systems and antibiotic residues in Bangladesh. The study spanned from December 2022 and April 2023 and was conducted in five Upazilas in the Mymensingh district of Bangladesh. During the study period, biological samples were analyzed to examine the presence of One Health significance antimicrobial resistant bacteria from Mymensingh district.